IRE1α Activation in Bone Marrow-Derived Dendritic Cells Modulates Innate Recognition of Melanoma Cells and Favors CD8+ T Cell Priming - Medel, Bernardita; Costoya, Cristobal; Fernandez, Dominique; Pereda, Cristian; Lladser, Alvaro; Sauma, Daniela; Pacheco, Rodrigo; Iwawaki, Takao; Salazar-Onfray, Flavio; Osorio, Fabiola (Frontiers in Immunology, 2019)
The IRE1α/XBP1s signaling pathway is an arm of the unfolded protein response (UPR) that safeguards the fidelity of the cellular proteome during endoplasmic reticulum (ER) stress, and that has also emerged as a key regulator of dendritic cell (DC) homeostasis. However, in the context of DC activation, the regulation of the IRE1α/XBP1s axis is not fully understood. In this work, we report that cell lysates generated from melanoma cell lines markedly induce XBP1s and certain members of the UPR such as the chaperone BiP in bone marrow derived DCs (BMDCs). Activation of IRE1α endonuclease upon innate recognition of melanoma cell lysates was required for amplification of proinflammatory cytokine production and was necessary for efficient cross-presentation of melanoma-associated antigens without modulating the MHC-II antigen presentation machinery. Altogether, this work provides evidence indicating that ex-vivo activation of the IRE1α/XBP1 pathway in BMDCs enhances CD8+ T cell specific responses against tumor antigens.